2013
DOI: 10.1080/00207543.2011.653449
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent product configuration and process planning, towards an approach combining interactivity and optimality

Abstract: In mass customisation, defining concurrently the configured product and the planning of the associated production process is a key issue in the customer/supplier relationship. Nevertheless, few studies propose supporting the decision-maker during the resolution of this significant problem. After studying the decision-maker's needs and problem characterisation (modelling and scale aspects), we propose in this paper a two-step approach with the aid of some tools. The first step allows the customer or internal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…In most of the presently developed concurrent design methods for mass customisation production, only design and one of the downstream product development life cycle aspects such as manufacturing process are considered Pitiot et al 2013). Quality of the mass customised product can be improved by incorporating considerations in more downstream product development life cycle activities such as manufacturing resource planning and maintenance process planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the presently developed concurrent design methods for mass customisation production, only design and one of the downstream product development life cycle aspects such as manufacturing process are considered Pitiot et al 2013). Quality of the mass customised product can be improved by incorporating considerations in more downstream product development life cycle activities such as manufacturing resource planning and maintenance process planning.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Huang, and Rungtusanatham (2008) developed a mixed integer programming model that integrated both platform product design and material purchase decisions based on cost drivers that were sensitive to commonality and modularity. Pitiot et al (2013) introduced a two-step approach to conduct concurrent product configuration and process planning, where the first step was to capture the customer or internal requirements interactively with a constraint-based approach and the second step was to identify the optimal solution through a multi-criteria constrained evolutional optimisation algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…With the previous problem descriptions, Pitiot, Aldanondo, and Vareilles (2014) and Pitiot et al (2012) have suggested (i) combining these two problems into a single one and (ii) considering this concurrent problem as a single CSP. Viewing this concurrent configuration problem as a single CSP allows propagation or constraint filtering mechanisms to be used as an aiding tool.…”
Section: Concurrent Configuration In Routine Situationsmentioning
confidence: 99%
“…Each time a customer's expectation is inputted (mainly in the product and less in the process), constraints propagate this decision and prune variables values for descriptive attributes, component families, resources families, resources quantities, operation duration and then update performance, cycle time and total cost. For a detail presentation with an easy to understand example, we deeply suggest to consult [13]. This kind of problem modeling is the ground basis of configuration problems.…”
Section: Offer Configurations In Ato-mto-eto Situationsmentioning
confidence: 99%